2020
DOI: 10.3390/ijms21041414
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of CLIBASIA_03915/CLIBASIA_04250 by Tobacco Mosaic Virus Resulted in Phloem Necrosis in the Senescent Leaves of Nicotiana benthamiana

Abstract: Huanglongbing (HLB), also known as citrus greening, is the most notorious citrus disease worldwide. Candidatus Liberibacter asiaticus (CaLas) is a phloem-restricted bacterium associated with HLB. Because there is no mutant library available, the pathogenesis of CaLas is obscure. In this study, we employed tobacco mosaic virus (TMV) to express two mature secretion proteins CLIBASIA_03915 (m03915) and CLIBASIA_04250 (m04250) in Nicotiana benthamiana (N. benthamiana). Phloem necrosis was observed in the senescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Moreover, several research groups have developed transient expression assays using virus‐based expression vectors. In these assays, genes of interest of various pathogens are expressed in N. benthamiana leaves using tobacco rattle virus (TRV) and potato virus X (PVX) expression vectors (Zhang et al, 2019a; Li et al, 2020). Over the past three decades, remarkable progress has been made in the development of plant viral vectors owing to their ease of manipulation (Hefferon, 2017).…”
Section: Figurementioning
confidence: 99%
“…Moreover, several research groups have developed transient expression assays using virus‐based expression vectors. In these assays, genes of interest of various pathogens are expressed in N. benthamiana leaves using tobacco rattle virus (TRV) and potato virus X (PVX) expression vectors (Zhang et al, 2019a; Li et al, 2020). Over the past three decades, remarkable progress has been made in the development of plant viral vectors owing to their ease of manipulation (Hefferon, 2017).…”
Section: Figurementioning
confidence: 99%
“…For example, CLIBASIA_03875 and CLIBASIA_04025 suppress programmed cell death (PCD) (Zhang et al, 2019;Pang et al, 2020), CLIBASIA_05315 targets the chloroplasts and induces cell death in Nicotiana benthamiana (Pitino et al, 2016(Pitino et al, , 2018 as well as physically interacting with the papain-like cysteine proteases (PL) and inhibiting their protease activity in citrus (Clark et al, 2018). In addition, a subset of Sec-dependent secretory proteins were deduced to be candidate effectors that play roles during CLas infection using a Tobacco mosaic virusbased expression system or a strategy for the analysis of temporal and spatial gene expression (Shi et al, 2019;Ying et al, 2019;Li et al, 2020). Recently, two non-classically secreted proteins, CLIBASIA_RS00445 and SC2_gp095, were shown to dramatically downregulate the gene expression of RbohB, a gatekeeper of H 2 O 2 -mediated defense signaling in Nicotiana tabacum (Jain et al, 2015(Jain et al, , 2018, and the former was also identified to suppress oxylipin-mediated defense in citrus plants (Jain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Liberibacter asiaticus secretes a minimum of 86 proteins via the general secretion system (Sec pathway) [15]. Many of these Sec-delivered effectors (SDEs) have different expression levels in citrus and psyllids to manipulate host responses [16][17][18]. Sec-delivered effector 1 (SDE1, also known as Las5315) is a protein composed of 154 amino acids and can be secreted to the extracellular space outside of the cell through the Sec pathway, upon expression in Escherichia coli [15].…”
Section: Introductionmentioning
confidence: 99%